2015
DOI: 10.1007/s10195-015-0376-5
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma versus autologous blood versus steroid injection in lateral epicondylitis: systematic review and network meta-analysis

Abstract: BackgroundClinical outcomes between the use of platelet-rich plasma (PRP), autologous blood (AB) and corticosteroid (CS) injection in lateral epicondylitis are still controversial.Materials and methodsA systematic review and network meta-analysis of randomized controlled trials was conducted with the aim of comparing relevant clinical outcomes between the use of PRP, AB and CS injection. Medline and Scopus databases were searched from inception to January 2015. A network meta-analysis was performed by applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 33 publications
4
111
0
4
Order By: Relevance
“…According to a network meta-analysis comparing PRP, corticosteroid, and AB injection, published in 2015, PRP improves pain and reduces the risk of complications, whereas AB improves pain, disability scores, and the pressure pain threshold but involves a higher risk of complications. 42 Nevertheless, Krogh and colleagues found that even though AB and PRP were significantly superior to placebo, only 1 trial was at low risk of bias. 18 The poor clinical outcomes found at 2 years in our study are consistent with other research findings showing that PRP is not effective in long-term pain reduction compared with steroid and placebo injection.…”
Section: Discussionmentioning
confidence: 97%
“…According to a network meta-analysis comparing PRP, corticosteroid, and AB injection, published in 2015, PRP improves pain and reduces the risk of complications, whereas AB improves pain, disability scores, and the pressure pain threshold but involves a higher risk of complications. 42 Nevertheless, Krogh and colleagues found that even though AB and PRP were significantly superior to placebo, only 1 trial was at low risk of bias. 18 The poor clinical outcomes found at 2 years in our study are consistent with other research findings showing that PRP is not effective in long-term pain reduction compared with steroid and placebo injection.…”
Section: Discussionmentioning
confidence: 97%
“…The cause of LE remains unclear. However, there is a common agreement that LE might be caused by repetitive strain to the extensor tendon, typically the extensor carpi radialis brevis tendon, and by overuse of the wrist. Patients with LE experience pain and lose elbow function.…”
Section: Introductionmentioning
confidence: 99%
“…Previous meta-analyses have drawn disparate conclusions regarding PRP efficacy, likely because of widely varying methodologies among studies. [32][33][34][35][36][37][38] We designed the current review to minimise potential sources of bias, namely by excluding non-randomised studies, studies with non-injection control groups, or active injectable controls (eg, whole blood, PRP). Still, we identified significant heterogeneity in treatment effects.…”
Section: Discussionmentioning
confidence: 99%